2005
DOI: 10.1021/ja042758e
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Epoxidation of a Terminal Alkene Containing Allylic Hydrogen Atoms: trans-Methylstyrene on Cu{111}

Abstract: The selective oxidation of trans-methylstyrene, a phenyl-substituted propene that contains labile allylic hydrogen atoms, has been studied on Cu{111}. Mass spectrometry and synchrotron fast XPS were used to detect, respectively, desorbing gaseous products and the evolution of surface species as a function of temperature and time. Efficient partial oxidation occurs yielding principally the epoxide, and the behavior of the system is sensitive to the order in which reactants are adsorbed. The latter is understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 34 publications
1
51
0
Order By: Relevance
“…In the present context, the ability of oxygenated silver surfaces to react with unsaturated organic adsorbates without totally disrupting them by deep oxidation-unlike the platinum group metals, which induce total combustion 14 [20][21][22][23][24] In this paper we report the first observation of the silver-catalyzed homocoupling of phenylacetylene on extended Ag(100) single crystal surfaces in vacuum and also the corresponding behavior of Ag particles in solution. STM and XPS single crystal results unambiguously established that the presence of chemisorbed oxygen was critical for efficient reaction to occur and that the crucial reaction-initiating step was abstraction of the acetylenic hydrogen atom by O(a), which caused the reaction to propagate over the entire metal surface, as opposed to being confined to island boundaries.…”
Section: Introductionmentioning
confidence: 90%
“…In the present context, the ability of oxygenated silver surfaces to react with unsaturated organic adsorbates without totally disrupting them by deep oxidation-unlike the platinum group metals, which induce total combustion 14 [20][21][22][23][24] In this paper we report the first observation of the silver-catalyzed homocoupling of phenylacetylene on extended Ag(100) single crystal surfaces in vacuum and also the corresponding behavior of Ag particles in solution. STM and XPS single crystal results unambiguously established that the presence of chemisorbed oxygen was critical for efficient reaction to occur and that the crucial reaction-initiating step was abstraction of the acetylenic hydrogen atom by O(a), which caused the reaction to propagate over the entire metal surface, as opposed to being confined to island boundaries.…”
Section: Introductionmentioning
confidence: 90%
“…C K-edge data were acquired at five angles of photon incidence (θ) at both coverages and the raw data were processed following standard methodology 16,17 by first extracting the integrated π* intensities and then analyzing their angular dependence. The spectra exhibit two sharp 1s π* resonances whose dependence on photon incidence angle is markedly different: they are assigned to the C=C bond (282.5 eV) and the C=O bond (284.3 eV), 13,15 the intensity of the latter transition decreased to almost zero at normal photon incidence, at which point substantial C=C intensity remained. From the well known selection rules for 1s π* transitions of adsorbates on (111) surfaces we may draw the qualitative conclusion that C=O bond is almost parallel to the metal surface whereas the C=C is appreciably tilted.…”
Section: Nexafs Of Crotonaldehydementioning
confidence: 96%
“…Further characterizations with high-resolution transmission electron microscopy (HRTEM) and Auger spectroscopy indicated that highly dispersed metal Cu NPs (\5.0 nm) might be responsible for PO formation. In addition, Lambert et al [87] found that model catalyst Cu(111) catalyzed the epoxidation of alkene containing allylic hydrogen (trans-methylstyrene) under ultrahigh vacuum conditions. Theoretical calculation suggested that in propene Fig.…”
Section: Copper Catalystsmentioning
confidence: 99%